Non-volant mammals of Mt. Hamiguitan, Eastern Mindanao, Philippines - Balete, Danilo S. (Banwa, 2006)
Sampling of various forest habitats along an elevational gradient from 200 m to 1128 m on Mt. Hamiguitan resulted in the capture of six species of non-volant small mammals, consisting of one shrew (Soricidae), one gymnure (Erinaceidae) and four rodents (Muridae). With the exception of an introduced, commensal rat, Rattus exulans, the rest of the species are native. Additionally, information gathered from local people and direct observation indicate the presence on the mountain of one species of tree-shrew (Tupaiidae), one flying lemur (Cynocephalidae), one primate (Cercopithecidae), three squirrels (Sciuridae), two civets (Viverridae), one wild pig (Suidae) and one deer (Cervidae). Strong association of the endemic species with primary and slightly disturbed forest, and the exclusive association of the pest species with open and severely degraded habitats, were noted. At least two species from the montane forest, based on preliminary examination, are potentially new to science, highlighting the importance of Mt. Hamiguitan as a unique center of endemism in the Philippines. Protection of representative montane forest habitats of the native species on Mt. Hamiguitan is recommended.